Nasotracheal Intubation in a Difficult Airway Using the Boedeker-Doerges Suction Blade Laryngoscope, Boedeker Bougie Endotracheal Introducer, and Boedeker Forceps - Thomas A. Nicholas; Ben Boedeker (Association of American Medical Colleges, 2011)
Abstract This web-based teaching module was constructed in order to describe a modified nasotracheal intubation technique. The module was constructed using original video, illustrations, and photos. It contains audio and text narration, which are based on recent literature review with citations. The module was deployed on our Web site for review by practitioners learning airway management. The module functions similar to a PowerPoint presentation with scrolling menu on the left side of the screen and a notes section. The viewer will allow for automatic or manual scrolling. This module will allow other medical providers to learn a different technique in managing a difficult airway. The multimedia and web-based characteristics will provide a strong learning tool for the medical provider.